2009
DOI: 10.1136/qshc.2008.029439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of quality strategies on hospital outputs

Abstract: Context: This study was part of the Methods of Assessing Response to Quality Improvement Strategies (MARQuIS) research project on patients crossing borders, a study to investigate quality improvement strategies in healthcare systems across the European Union (EU). Aim: To explore the association between the implementation of quality improvement strategies in hospitals and hospitals' success in meeting defined quality requirements that are considered intermediate outputs of the care process. Methods: Data regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 16 publications
1
34
0
8
Order By: Relevance
“…Latent failures remain "asleep" in this system and are related to organizational influences, unsafe supervision and predisposition to unsafe acts. (14) Another important aspect of the study was the finding that a great part of causal factors of falls was affected by the absence of protocol of fall prevention within the studied institution.…”
Section: Discussionmentioning
confidence: 99%
“…Latent failures remain "asleep" in this system and are related to organizational influences, unsafe supervision and predisposition to unsafe acts. (14) Another important aspect of the study was the finding that a great part of causal factors of falls was affected by the absence of protocol of fall prevention within the studied institution.…”
Section: Discussionmentioning
confidence: 99%
“…Az akkreditációs rendszerek diverzifitása visszavezethető az országok eltérő erőforrásból gazdálkodó, eltérő szükségletekre tervezett egészségügyi rendszereinek különbözőségére [11,14]. Bár az akkreditáció eredmé-nyességének kutatása jelenleg is több kutatócsoport ér-deklődésének középpontjában áll, feltételezhetően a helyi sajátosságokhoz igazítottsága teszi képessé arra, hogy bizonyítottan szignifikáns mértékben javítsa az ellátás minőségét és a betegbiztonságot [15].…”
Section: Az Egészségügyi Akkreditáció Jellemzői éS Jelentőségeunclassified
“…Studies of 89 European hospitals indicate that accreditation and International Organization for Standardization (ISO) 9001 certification are positively associated with some quality and safety structures and hospital outputs such as hospital management, clinical practice, safety, patient-centeredness and cross-border patient-centeredness. These studies demonstrated that accreditation has slightly more impact than ISO certification, but either system is better than no external assessment [11,12]. The recent EU project DUQUE with data from 73 European hospitals studied the relationship between ISO 9000 certification, healthcare accreditation, and quality management.…”
Section: Introductionmentioning
confidence: 99%